Answer:
The solution set is {-2, 3}.
Explanation:
We can do this by elimination after manipulating the 2 equations so that the coefficients of y will disappear after addition:
5x - 2y = -16 Multiply this by -5:
-25x + 10y = 80 ...........(A)
4x - 5y = -23 Multiply this by 2:
8x - 10y = -46..............(B)
Now add A and B:
-17x = 34
x = 34/-17
x = -2.
Now substitute x = -2 into the first original equation:
5(-2) - 2y = -16
-2y = -16 +10 = -6
y = -6/-2
y = 3.
Confirm these results by substitution in the second original equation:
4(-2) - 5(3)
= - 8 - 15 = -23.
Checks OK.